Innovative Use of High-Fidelity Lung Simulators to Test a Ventilator Splitter Device - Boyer, Tanna J. (A A Pract, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has rapidly exposed health care system inadequacies. Hospital ventilator shortages in Italy compelled US physicians to consider creative solutions, such as using Y-pieces or T-pieces, to preclude the need to make decisions of life or death based on medical equipment availability. We add to current knowledge and testing capacity for ventilator splitters by reporting the ability to examine the functionality of ventilator splitters by using 2 high-fidelity lung simulators. Data obtained by the high-fidelity lung simulators included: tidal volume, respiratory rate, minute ventilation, peak inspiratory pressure, peak plateau pressure, and positive end-expiratory pressure.